MAKTABGACHA TA’LIM TAShKILOTLARIDA INTERAKTIV O‘QUV MAJMUALARIDAN FOYDALANISh - Allambergenova, M.X. (SCIENCE and SOCIETY, 2025)
This article examines the use of interactive educational complexes for preschool educational institutions today and their importance.
Keywords: preschool education; electronic resources; information technology; electronic manuals; multimedia programs; interactive educational and methodological complex